2011
DOI: 10.1186/ar3548
|View full text |Cite
|
Sign up to set email alerts
|

Notochordal cells protect nucleus pulposus cells from degradation and apoptosis: implications for the mechanisms of intervertebral disc degeneration

Abstract: IntroductionThe relative resistance of non-chondrodystrophic (NCD) canines to degenerative disc disease (DDD) may be due to a combination of anabolic and anti-catabolic factors secreted by notochordal cells within the intervertebral disc (IVD) nucleus pulposus (NP). Factors known to induce DDD include interleukin-1 beta (IL-1ß) and/or Fas-Ligand (Fas-L). Therefore we evaluated the ability of notochordal cell conditioned medium (NCCM) to protect NP cells from IL-1ß and IL-1ß +FasL-mediated cell death and degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 35 publications
6
137
0
Order By: Relevance
“…Unpublished work by our group indicates that also no difference in biologic activity was established between canine NCCM that was generated under NX or HX conditions. In agreement with our studies, previous work demonstrating the regenerative potential of porcine and canine NC-secreted factors have used NCCM generated under HX (Abbott et al, 2012;Purmessur et al, 2011) and NX (Aguiar et al, 1999;Boyd et al, 2004;Erwin et al, 2011;Korecki et al, 2010) conditions. Altogether, this may imply that oxygen status during NCCM generation does not result in a differential biologic activity of NC-secreted factors on human CLCs.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Unpublished work by our group indicates that also no difference in biologic activity was established between canine NCCM that was generated under NX or HX conditions. In agreement with our studies, previous work demonstrating the regenerative potential of porcine and canine NC-secreted factors have used NCCM generated under HX (Abbott et al, 2012;Purmessur et al, 2011) and NX (Aguiar et al, 1999;Boyd et al, 2004;Erwin et al, 2011;Korecki et al, 2010) conditions. Altogether, this may imply that oxygen status during NCCM generation does not result in a differential biologic activity of NC-secreted factors on human CLCs.…”
Section: Discussionsupporting
confidence: 80%
“…NCCM of all species, generated under identical conditions on the basis of wet NP weight, increased CLC cell numbers and GAG deposition, but canine and porcine NCCM appeared more potent than human NCCM. Although the IVD is an avascular hypoxic structure and several studies have demonstrated that NCs respond superior to hypoxic than normoxic culture conditions (Erwin et al, 2009;Omlor et al, 2014), no difference in regenerative potential was found between human NCCM generated under HX or NX conditions. Unpublished work by our group indicates that also no difference in biologic activity was established between canine NCCM that was generated under NX or HX conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notochordal cells have been shown to produce more proteoglycans than smaller NP cells [69] and, when in coculture, notochordal cells interact with small NP cells stimulating them to produce a healthier extracellular matrix [70,71]. Recent findings also show that notochordal cells can prevent Il-1-induced cell death in small NP cells [72]. Therefore, defining the notochordal cell phenotype and tracking these cells in human discs would also allow clarifying their role in the disc's physiology and disease.…”
Section: T (Brachyury) Ratmentioning
confidence: 99%
“…The NP is surrounded by the AF, and is a gel-like structure that contains chondrocyte-like cells (Bowles et al, 2011;Dahia et al, 2012). During IVD, NP cells decrease in number and the remaining cells have an altered phenotype that is associated with an increased breakdown of the extracellular matrix and altered matrix synthesis (Urban et al, 2004;Skubutyte et al, 2010;Erwin et al, 2011). Traditional treatment options for managing IVD mainly include conservative and surgical treatments.…”
Section: Introductionmentioning
confidence: 99%